Cost analysis of eye bank versus surgeon prepared endothelial grafts - Luca Pagano; Kunal A Gadhvi; Mohit Parekh; Giulia Coco; Hannah J Levis; Diego Ponzin; Stefano Ferrari; Gianni Virgili; Stephen B Kaye; Rhiannon T Edwards; Vito Romano (BMC, 2021)
Abstract Background Selective lamellar corneal transplantation (keratoplasty) has overtaken full thickness penetrating keratoplasty as the graft choice for endothelial failure. Even more recently eye bank prepared tissues are becoming increasing popular as a way to reduce the risks of tissue loss and stress during endothelial keratoplasty preparation in the surgical theatre. This study compares costs between surgeon and eye bank prepared tissues for Descemet's stripping automated endothelial keratoplasty (DSAEK) and Descemet's membrane endothelial keratoplasty (DMEK). Methods Retrospective study conducted at the Royal Liverpool University Hospital including endothelial keratoplasties with a minimum of 6 months follow-up time. Cost analysis included surgical expenses, tissue acquisition fees, cost of patient's ward admission and out-patient expenses, including cost of re-bubbling procedures, costs of visits, anterior segment imaging and optometrist visits within the first 6 months follow-up. Results Ninety-eight eyes of 98 patients were included in the study of which 42 underwent DSAEK surgery and 56 DMEK surgery. Cost analysis of surgical expenses in the DSAEK group showed a significant difference between using surgeon prepared and eye bank prepared tissue (£3866 ± 296 and £4389 ± 360, respectively; p < 0.01) and the same was found in the DMEK group (£3682 ± 167 and £4162 ± 167 for surgeon prepared and eye bank prepared tissues, respectively; p < 0.01). Cost of out-patient visits did not differ significantly in either group. Conclusions At the Royal Liverpool University Hospital, eye bank prepared tissues had higher surgical expenses compared to those prepared by the surgeon, while the post-operative care expenses were similar between the two groups.